Higher Levels of Income and Education are Associated with More Specialized Sport Participation Behaviors: Results from a Representative Sample of Youth Sport Parents from the United States - Eric G Post; Matthew J. Rivera; Darleesa Doss; Lindsey E. Eberman (International Journal of Sports Physical Therapy)
# Background